Eritrea - The Process of Capturing Indigenous Knowledge - Pidatala, Krishna (World Bank, Washington, DC, 2012)
Eritrea is a country with rich indigenous culture and traditional practices. It is often difficult to discern indigenous knowledge (IK) embedded in community practices, institutions, relationships, and rituals due to its tacit nature. Many countries have recently recognized the threat of losing IK and are putting together initiatives aimed at preservation and revitalization of this valuable resource. In 1982, a group of Eritreans launched a scheme to identify and document their local knowledge. The initiative was conceived to be carried out in two phases: collection of IK information, and detailed validation and analysis. The purpose was to study the cultures and traditional practices of the ethnic nationalities and capture, categorize and document these for subsequent preservation and publication. This Note describes the process, analyzes the constraints and impact, and discusses the next steps.